ETHNOPSYCHOLOGICAL ANALYSIS OF STRUCTURAL PECULIARITIES IN SUBJECTIVE WELL-BEING(a case study of ethnic groups of the Saratov Region) - E E Bocharova (Peoples' Friendship University of Russia (RUDN University), 2016)
The article presents the data of the empirical study of the structural organization of ethnic groups subjective well-being on the territory of the Saratov Volga region conducted on proportionally selected samples ( N = 280), whose representatives identify themselves as Russians ( n = 70; city of Saratov), Armenians ( n = 70; city of Saratov), Kazakhs ( n = 70; village Alexandrov Ghay in the Saratov Region that borders on the West Kazakhstan Region of Kazakhstan with the ethnical composition represented primarily by Kazakhs), Tatars ( n = 70; village Yakovlevka in Bazarno-Karabulakskiy district of the Saratov Region with the Tatar dominant ethnical group), whose average age is 25.6 years old; SD = 9.7; sex ratio is female (52%) and male (48%); respondents' employment - 87%. It has been found that in contrast to the Russians, the sphere of social and socio-economic relations is the least "happy" area in the representatives of the Armenian, Kazakh, Tatar ethnic groups. The "happiest" is the sphere of family relations in the samples of Armenian, Kazakh and Tatar youth. The significant differences have been revealed in the structure of the subjective well-being both on the emotional and cognitive levels. A downward trend of the index of the subjective well-being of the ethnic groups from the remote areas of the region has been registered. The applied aspect of the research problem can be implemented in the development of ethno-national policy programmes of the Saratov region.